Clinical and cytogenetic characteristics of patients diagnosed with Turner syndrome in a clinical genetics service: cross-sectional retrospective study - Nunes, Maurício Rouvel; Pereira, Tiago Godói; Correia, Henry Victor Dutra; Canabarro, Simone Travi; Vanz, Ana Paula; Zen, Paulo Ricardo Gazzola; Rosa, Rafael Fabiano Machado (São Paulo Medical Journal, 2021)
BACKGROUND: Turner syndrome (TS) is a rare genetic disease. Understanding its clinical findings contributes to better management of clinical conditions. OBJECTIVE: To investigate the clinical and karyotypic characteristics of patients diagnosed with TS at two reference services for clinical genetics in southern Brazil. DESIGN AND SETTING: Retrospective cross-sectional study conducted in two clinical genetics services in Porto Alegre (RS), Brazil. METHODS: The sample consisted of 59 patients with TS diagnosed from 1993 to 2019. A review of their medical records was performed and a standard protocol was filled out. RESULTS: The average age of the patients at diagnosis was 15.9 years, and 40.7% were over 13 years old. The largest proportion of them (42.4%) had been referred from an endocrinology department and their constitution was 45,X (40.7%). The most common clinical findings were short stature (85.7%), hypoplastic/hyperconvex nails (61.2%), low posterior hairline (52.1%) and cubitus valgus (45.8%). There was no difference regarding the presence of short stature (P = 0.5943), number of dysmorphia (P = 0.143), anatomical regions affected and malformations identified through imaging examinations (P = 1.0000), regarding the presence or absence of 45,X constitution. Only 6% of the patients had used growth hormone and 43%, estrogen. CONCLUSION: We found that, in general, patients with TS were being diagnosed late. This has important implications for their treatment. In addition, only a small proportion of the patients were undergoing further examination or evaluation, which appeared to be leading to underdiagnosis of many abnormalities.